Experimental and numerical studies of S960 ultra-high strength steel welded I-sections under combined compression and minor-axis bending - Su, Andi (2022)
The present paper reports comprehensive experimental and numerical investigations into the cross-section behaviour and resistances of S960 ultra-high strength steel welded I-sections under combined compression and minor-axis bending moment. An experimental programme, adopting two slender welded I-sections – I-120 × 120 × 6 and I-150 × 75 × 6, was firstly conducted and included initial local geometric imperfection measurements and ten minor-axis eccentric compression tests. A numerical modelling programme was then performed, where finite element models were firstly developed and validated against the test results and then employed to perform parametric studies to generate further numerical data over a wide range of cross-section dimensions and loading combinations. On the basis of the test and numerical data, the applicability of the design interaction curves for S700 (or S690) high strength steel welded I-sections under minor-axis combined loading, as set out in the European code, American specification and Australian standard, to their S960 ultra-high strength steel counterparts was evaluated. The evaluation results generally revealed that all the codified design interaction curves lead to unduly conservative and scattered cross-section resistance predictions, mainly owing to the adoption of conservative bending end points (i.e. cross-section bending capacities).